2013
DOI: 10.1073/pnas.1217335110
|View full text |Cite
|
Sign up to set email alerts
|

Cleaved-coupled nanowire lasers

Abstract: The miniaturization of optoelectronic devices is essential for the continued success of photonic technologies. Nanowires have been identified as potential building blocks that mimic conventional photonic components such as interconnects, waveguides, and optical cavities at the nanoscale. Semiconductor nanowires with high optical gain offer promising solutions for lasers with small footprints and low power consumption. Although much effort has been directed toward controlling their size, shape, and composition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 31 publications
0
107
0
Order By: Relevance
“…Our results showed that the AlGaAs shell inhibits nonradiative surface recombination such that clear near-infrared lasing operation can be achieved up to room temperature in this important materials system. The highly nonlinear input-output emission characteristics have strong potential for novel applications in which lasing is used to optically sense the local environment of the NW 34 or in the use of coupled cavity concepts for switching 35 . Although one can expect further improvements of the NW-laser performance by improving the end-facet reflectivity via chemical polishing or by placing them onto patterned substrates for which distributed feedback concepts can be exploited 36 , the direct integration of III/V NW lasers onto silicon substrates for integrated photonics and optical interconnects 37 remains a significant challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the AlGaAs shell inhibits nonradiative surface recombination such that clear near-infrared lasing operation can be achieved up to room temperature in this important materials system. The highly nonlinear input-output emission characteristics have strong potential for novel applications in which lasing is used to optically sense the local environment of the NW 34 or in the use of coupled cavity concepts for switching 35 . Although one can expect further improvements of the NW-laser performance by improving the end-facet reflectivity via chemical polishing or by placing them onto patterned substrates for which distributed feedback concepts can be exploited 36 , the direct integration of III/V NW lasers onto silicon substrates for integrated photonics and optical interconnects 37 remains a significant challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Mode selection was performed and only one mode was stimulated at the end using two GaN nanowires coupled side by side [110]. Yang et al from Berkeley University followed the same principles, except for performing the coupling axially rather than radially [29]. This technique extended the existing concept of a cleaved-coupled cavity (C3) from conventional ridge laser diodes to nanowire lasers.…”
Section: (C) Single-mode Selectionmentioning
confidence: 99%
“…The consequent next step beyond the proof of nanowire lasing is the modification of the emission, for example by adjusting the resonator properties with a focused ion beam machine (FIB) to create coupled cavity NW lasers [18] or loop resonators [19]. Cadmium sulfide (CdS) nanowire lasers bridge the green spectral region around 2.4 eV, provide excellent optical mode confinement [20] and form quasi 1D optical systems with diameters between 150 nm -500 nm.…”
Section: Introductionmentioning
confidence: 99%